Analysis of illuminance level on phinisi tower building - Jamala, Nurul; Rahim, Ramli; Mulyadi, Rosady (Penerbit Universiti Kebangsaan Malaysia, 2019)
Lighting design in buildings is one of the determinants of success. Sunlight is a natural resource that is used daily for use that will produce energy in the building. The purpose of this study is to analyze the space that is directly related to the spaces associated with different spaces. The research method is quantitative with data that underlies the results and is very clear in the form of linear graphs, bar charts, and rounds. Results of research conducted during the day Illumination values in the oriented space to the north are higher than south orientation. The closest area to the building envelope has the highest illumination value. The results of this analysis can determine the illumination values that exist for building satisfaction. Furthermore, further from the opening of the building envelope, the illumination value decreases. The constitution is one of the guidelines in the context of building.